The Influence of Organizational Culture and Welfare on The Work Effectiveness of USK Employees - Saifan Saifan; Murniati Murniati; Nasir Usman (Asian Journal of Social and Humanities, 2024)
An organization is a forum in which there are activities of people working together to achieve a certain goal that has been determined together. This study aims to examine the influence of organizational culture and welfare on the work effectiveness of USK employees. The research method used is a survey using a questionnaire distributed to employees at the USK administrative headquarters. The collected data was analyzed using descriptive statistical and regression methods. The results of the study show that there is a positive relationship between strong organizational culture and employee welfare and employee work effectiveness. The influence of organizational culture on the work effectiveness of USK employees is 70.48%, which shows that organizational culture has a significant influence on the work effectiveness of employees at USK. While the influence of welfare is 66.76%, this shows a fairly good level of approval for the effectiveness of employee work. The combination of a strong organizational culture and employee well-being creates greater synergy in increasing work effectiveness. The influence of a strong and positive organizational culture significantly increases the effectiveness of employee work and the influence of employee welfare includes aspects such as fair compensation, a safe work environment, and contributes to increasing employee motivation and productivity. The implications of these findings show the importance of paying attention to organizational culture that allows employee participation and well-being in improving overall organizational performance.